After the pandemic: securing smart cities. Issue 11 (November 2021) - Curran, Kevin
Abstract : Covid-19 has forced us all to rethink the way we live, work and socialise, with technology proving how vital it has become to cities and how have they responded to the pandemic. Indeed, innovations such as the Internet of Things (IoT), 5G and location-based services have been used to help minimise the risk of transmission, maintain social distancing measures and ensure the continuation of vital services.